First Report Of New Delhi Metallo-Beta-Lactamase (NDM) Producing Citrobacter Braakii Isolated From Diabetic Foot Infection In Iraq - Zuhair Wahid, Huda; Jaber Hadi, Zainab; Fadhil Abdul-ula, Maryam (Medical Science Journal for Advance Research, 2022)
Background: Diabetic foot infection (DFI) is an infection in soft tissue or bone in patient with diabetes mellitus, Citrobacter species are infrequent nosocomial pathogens and cause a range of infections. the aim of the current study we report the isolation of carbapenem genes among Citrobacter species isolated from DFI. Methods: about 111 swabs specimen were collection from patient suspected with DFI during the period of study, determine the antibiotic susceptibility of Citrobacter spp isolates by using Kirby-Bauer disk diffusion method to 23 antimicrobial agents according to the CLSI (2021). Molecular detection for MBL genes by multiplex PCR. Results: from 111 swabs specimen Citrobacter spp isolates had represented in 3 (4.34%) among Gram-negative bacteria. Antibiotic susceptibility test revealed that one isolate of Citrobacter braakii was MDR and the other isolates was PDR. The PCR data of MBL genes revealed that the frequency of MBL genes among Citrobacter braakii as following blaVIM, blaNDM, and blaSIM were 100%. Conclusion: the study show the appear MDR and PDR among Citrobacter species and Citrobacter braakii isolate carry the MBL genes (blaVIM, blaNDM, and blaSIM) where the dissemination of NDM producing Citrobacter braakii considered first reported in Iraq.